Training on Making Dadih from Goat's Milk to Overcome the Problem of Stunting in Deli Serdang Regency - Ginting, Nurzainah (Journal of Saintech Transfer, 2023)
According to the 2021 Indonesian Toddler Nutrition Status Survey, North Sumatra Province reported the fifth-highest number of children with stunting in Indonesia, totaling 383,403 stunted toddlers. Stunting is also prevalent in Deli Serdang Regency. The problem of stunting is a nutritional problem whose phenomenon spreads at all levels. Stunting or a condition of growth failure in children under five due to chronic malnutrition, especially in the first 1000 days of birth. The community service has been carried out in STM Hilir subdistrict, Deli Serdang Regency. In this community service, the target characteristics are community of mothers who are also members of the â€œPKKâ€ (Empowerment and Family Welfare) of STM Hilir District with 150 members including staff of Integrated Health Post (â€œPosyanduâ€). The objectives of this community service were to teach about stunting so that mothers know how to avoid stunting and to teach how to make dadih enriched with various original flavours such as red guava, durian and banana. Participatory training and community empowerment were used as the methods in this community service activity. A comprehensive discussion occurred where mothers not only inquired about stunting but also delved into various topics. The results of this community service activity indicate an improvement in the community's knowledge about the production and benefits of dadih as a probiotic. The community also expresses a liking for the dadih products. Based on these findings, it is expected that the producing of dadih by the community can address issues related to stunting